Prevalence and determinants of Small Intestine Bacterial Overgrowth (SIBO) and carbohydrate intolerance in symptomatic Functional Bowel Disorder (FBD) - Siong, Sufian Chong Chern (2020)
Symptomatic Functional Bowel Disorder (FBD) has been a quite common presentation to the healthcare personnel. These patients often have other conditions that co-exist, such as Small Intestinal Bacterial Overgrowth (SIBO) and carbohydrate intolerance. SIBO and carbohydrate intolerance tend to worsen the symptoms of FBD. With the hydrogen breath test readily available nowadays, we can easily diagnose SIBO and carbohydrate intolerance. The test is rather simple and safe. This allow us to tackle the issue of refractory FBDs and improving the symptoms of those who has FBDs. This retrospective cross-sectional study involved all subjects who were more than 12 years old and had undergone hydrogen breath test at Hospital Universiti Sains Malaysia (HUSM) Kubang Kerian from 1st January until 1st July 2019. The data were obtained from the subject’s medical record. We analysed the prevalence of SIBO and carbohydrate intolerance. We also analysed the associated factors using simple and multiple logistic regression. A total of 104 subjects were analysed. Among the 104 subjects, females were 51.9% (n=54), and males were 48.1% (n=50). The mean age of all the participants was 49.76 years old. The prevalence of SIBO, fructose intolerance /malabsorption, and lactose intolerance /malabsorption were 20%, 39% and 66% respectively. There were significant association between age (p≤0.050) and diabetes mellitus (p<0.001) with SIBO. There were no significant association factors found for the carbohydrate intolerance. It appears that lactose intolerance /malabsorption has higher prevalence in FBD compared to fructose intolerance /malabsorption and SIBO in this study. Not many significant associated factors for the three conditions that we studied were obtained.